Optimizing the Storage of Entomopathogenic Nematodes: Interaction of Media Types and Temperature Regimes on Viability and Virulence - Irwanto Sucipto; Mahendra Wahyu Waluyo Jati; Wildan Muhlison; Hari Purnomo (Jurnal Penelitian IPTEKS, 2026)
Entomopathogenic nematodes (EPN) are a vital biological agent in integrated pest management, yet maintaining their quality during storage remains a technical challenge . Objective: This study aimed to evaluate the efficacy of various storage media and temperature regimes in preserving the viability and virulence of EPN . Methods: A completely randomized factorial design was employed to test three storage media (active sodium alginate, passive polyurethane sponge, and water control) under two temperature conditions (15°C and 27°C) . Results: The study revealed that water media at 15°C (F0T1) maintained the highest viability, whereas sodium alginate at 15°C (F1T1) demonstrated superior retention of virulence by the fourth week . Conclusion: Low-temperature storage is critical for EPN survival, while active media formulations like sodium alginate offer significant advantages in preserving nematode pathogenicity for longer durations compared to passive media.